ASSOCIATION NOTES. - Austin, E. Burl (The Accounting Review, 1949)
Abstract The article presents information related to the field of accounting. In December, 1947, the Association of University Teachers of Accounting was formed. The Secretary advises that, until this group was formed, there existed in Great Britain no organization which was the counterpart of the American Accounting Association. The list of members is very small, by comparison, about thirty in number, but nevertheless includes virtually all university teachers of accounting in England and Scotland. At a recent meeting in Fort Worth of the Texas Association of University Instructors in Accounting, the following officers were elected President, O.J. Curry, North Texas State College; Vice-President, Charles Zlatkovitch, University of Texas; Secretary-Treasurer, Zeb B. Freeeman, Southern Methodist University. D. M. Beights served on the summer school staff at University of North Carolina, conducting a special course under joint sponsorship of the University and the North Carolina Society of Certified Public Accountants.